Club Penguin de Disney: los nuevos modos de construcción social de la infancia (2015)
Product of certain historical ambiguity about the place of children in society, in the twentieth century a notion of childhood associated with promoting safe spaces for their personal, social and educational development was built. In this context. The media emporium Disney arises which aims in the new millennium to new horizons. The MMO (Massively Multiplayer Online) for children. Proof of this was the acquisition by that company, of Club Penguin, a platform that has over 12 million registered users. In this paper, the construction of reality that children do in Club Penguin is analyzed, and their ways of interacting and communicating in a virtual world mediated by consumption, control and multiple conceptions of territory. Similarly, the study addresses how parents understand cyberspace and why Disney is configured as a synonym of trust or protection for their children. The Club Penguin analysis is done from a critical stance in order to demonstrate the degree of penetration of the Disney speech in an early age, which is masked in a MMO that despite offering a high degree of security against dangers such as cyberbullying, also broadcasts ideological components that can become harmful.